Sztuczna inteligencja a niebezpieczeństwo „inteligentnego” totalitaryzmu - Blicharz, Jolanta (Wydawnictwo Uniwersytetu Wrocławskiego, 2023)
The aim o the article is to consider the potential influence of artificial intelligence on thedevelopment of intelligent totalitarianism. The enhancement of surveillance and monitoring is one of the most important applications of artificial intelligence. The transformative power of artificial intelligence, however, is associated not only with the promised advantages in terms of development opportunities in many areas of economic and social life, but also with problems related, among others, to the loss of privacy. The dangerous power of mass surveillance, therefore, does not reside only in the totalitarian regimes of the past. In particular, the emergence of artificial intelligence has the potential to lead to intelligent totalitarianism as being particularly effective in enforcing its ideological vision preventing internal and external threats to its power by utilizing this modern technology.
Keywords: totalitaryzm; inteligentny totalitaryzm; sztuczna inteligencja; interfejs mózg–komputer; totalitarna ideologia